2015
DOI: 10.5194/acp-15-9203-2015
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric new particle formation as a source of CCN in the eastern Mediterranean marine boundary layer

Abstract: Abstract. While cloud condensation nuclei (CCN) production associated with atmospheric new particle formation (NPF) is thought to be frequent throughout the continental boundary layers, few studies on this phenomenon in marine air exist. Here, based on simultaneous measurement of particle number size distributions, CCN properties and aerosol chemical composition, we present the first direct evidence on CCN production resulting from NPF in the eastern Mediterranean atmosphere. We show that condensation of both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 62 publications
6
42
1
Order By: Relevance
“…Many of the previous studies showed diurnal cycles of particle hygroscopicity, with peaks typically appearing in the afternoon in urban [ Crosbie et al , ], rural [ Cerully et al , ], marine [ Kalivitis et al , ], boreal forest, and grassland areas [ Paramonov et al , ]. This has been explained by atmospheric aging of aerosols through condensational growth of photochemically oxidized organics and sulfate.…”
Section: Resultssupporting
confidence: 91%
“…Many of the previous studies showed diurnal cycles of particle hygroscopicity, with peaks typically appearing in the afternoon in urban [ Crosbie et al , ], rural [ Cerully et al , ], marine [ Kalivitis et al , ], boreal forest, and grassland areas [ Paramonov et al , ]. This has been explained by atmospheric aging of aerosols through condensational growth of photochemically oxidized organics and sulfate.…”
Section: Resultssupporting
confidence: 91%
“…Regarding ambient measurements, simultaneous measurements of sulfuric acid, sub‐3 nm particles, and oxidation products of BVOCs are very limited. However, observations have shown that even at temperatures above 300 K and at high RH above 60%, NPF still takes place at various atmospheric environments under high CS conditions, such as in Ohio, Taiwan, China, India, and the Mediterranean [ Erupe et al ., ; Kalivitis et al ., ; Kamra et al ., ; Kanawade et al ., , ; Qi et al ., ; Young et al ., ]. In Kent (Ohio), NPF took place during the summer with moderate sulfuric acid concentrations (at 10 6 cm −3 ), and the NPF days had warmer temperatures (>300 K) than the non‐NPF days [ Erupe et al ., ; Kanawade et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…At Finokalia, aerosol particle size distributions were measured in the size range 9-849 nm with a time resolution of 300 s with a custom-made scanning mobility particle sizer (SMPS) (Wiedensohler et al, 2012). As previously described by Kalivitis et al (2015), the system operates with a closedloop sheath air flow with a 5 : 1 ratio between the sheath and the aerosol flow. It comprises a Kr-85 aerosol neutralizer (TSI 3077), a Hauke medium differential mobility analyzer (DMA), and a TSI-3772 condensation particle counter (CPC).…”
Section: Ground-based Measurementsmentioning
confidence: 99%
“…Although the Mediterranean area is particularly sensitive to the future evolution of atmospheric pollutants and climate change, only a few studies related to NPF in this area have been reported so far. Intensive campaigns were conducted on the eastern Spanish coast, in Barcelona and at the Montseny site (Pey et al, 2008;Cusack et al, 2013), while long-term measurements are performed at the Finokalia (Crete) station (Kalivitis et al, 2008(Kalivitis et al, , 2015Manninen et al, 2010;Pikridas et al, 2012), where NPF event days are close to 30 %. The Mediterranean Basin is at the cross section of many different influences: there is a strong anthropogenic influence from densely populated coastal zones, in addition to marine and dust sources, as well as with emissions from Mediterranean forests and shrublands that emit both terpenes and isoprene.…”
Section: Introductionmentioning
confidence: 99%